Empowering Students’ Scientific Literacy Using Local Wisdom- Based Ethnobotany Atlas Media - Yuni Gayatri; Sela Rizqiyah; Peni Suharti (Jurnal Penelitian Pendidikan IPA, 2023)
Students' scientific literacy is influenced by various factors, including the choice of teaching materials used at school. An ethnobotanical atlas based on local wisdom is a collection of information or images that identify and document plants that exist around a particular community's residence or area, which can also be used by humans as food, medicine and so on. This research aims to determine the influence of ethnobotanical atlas media based on local wisdom on students' scientific literacy. This research is a pre-experimental research with a one group pretest-posttest design. The research sample was students of class X MIA 1 SMA Muhammadiyah 1 Surabaya. The data collection technique uses a written test. Data analysis was carried out statistically using normality tests, homogeneity tests, T and N gain tests. The results of the analysis showed that the data was normally distributed. The results of the T test show a significant effect of using ethnobotanical atlas media based on local wisdom on students' scientific literacy with a significance level of 0.000<0.05. Meanwhile, the results of the N-Gain test show that the use of ethnobotanical atlas media based on local wisdom is quite effective in increasing scientific literacy and can be alternative learning resource